Modified Risk Factors for Coronary Heart Disease (CHD) in Minahasa Ethnic Group From Manado City Indonesia - Nelwan, Ester Jeini; Widjajanto, Edi; Andarini, Sri; Djati, M. Sasmito (Graduate School, Universitas Brawijaya, 2016)
Coronary heart disease (CHD) is a non-transmitted disease which is particular concern at the global, national, and local level. CHD has become a concern because it has caused a lot of deaths. Risk factors linked with CHD consist of permanent risk factors and variable risk factors. The purpose of the research is to analyze the correlation between variable risk factors and CHD in the Minahasa ethnic society in Manado City. This research was an observational case-control study conducted by Prof. dr. R. D. Kandou Hospital, Manado, from August to October 2016. In total, there were 220 patients included. The sampling used a simple random sampling method and the data obtained were analyzed by chi-squared test. According to the results, hypertension, smoking, and behavioral type were connected to cases of CHD. The correlation degree showed that the respondents suffering hypertension were 5.70 times more likely to suffer CHD, the smoking respondents were 2.25 times more likely to experience, and behavior type A respondents were 2.96 times more likely to suffer CHD. Hypertension, smoking, and behavioral type are linked with CHD, so there should be some promotion and preventive actions from the health governmental institution to society, especially aimed at adults, about the quality of life enhancement by healthy behavior and avoiding CHD risk factors. Keywords: behavioral type, Case-control study, hypertension, smoking behavior.